Informed Refusal as an Application for The Protection of Patients' Human Rights and Legal Protection for Doctors and Health Workers in Health Services From A Criminal Law Perspective - Handrian Rahman Purawijaya; Jollis Jollis; Aswan Aswan (Riviera Publishing, 2025)
Health services are a basic right of every citizen guaranteed by law. In practice, patients not only have the right to consent to informed consent, but also the right to refuse the medical procedure through informed refusal, after receiving adequate information. Informed refusal is a form of respect for the patient's autonomy and has the same legal status as informed consent. However, the understanding and regulation related to informed refusal in Indonesia is still limited. This paper highlights the importance of legal recognition of informed refusal as part of human rights and the need for special regulations to realize legal certainty in the relationship between patients and health workers.